Traditional Diet and Environmental Contaminants in Coastal Chukotka IV: Recommended Intake Criteria - Dudarev, Alexey A. (Int J Environ Res Public Health, 2019)
The article is the last in the series of four that present the results of a study on environmental contaminants in coastal Chukotka, conducted in the context of a multi-disciplinary investigation of Indigenous foodways in the region. The article presents the Recommended Food Daily Intake Limit (RFDIL) guidelines of the locally harvested foods in coastal Chukotka. The guidelines were developed based on the results of the analysis of the legacy persistent organic pollutants (POPs) and metals found in the samples of locally harvested food, which was collected in 2016 in the villages of Enmelen, Nunligran, and Sireniki on the south coast of the Chukchi Peninsula, Russian Arctic. The overall aim of the article is to expand the toolset for dealing with the challenges of: (1) setting the dietary recommendations when we assess multiple contaminants in a variety of foods (and our method of RFDILs calculation is an example of a possible approach), and (2) managing the real-life circumstances when many types of foods are mixed in many dishes regularly and the concentrations of contaminants in these mixed dishes become uncertain. Drawing on perspectives from the fields of environmental health sciences, humanities, social sciences, and visual art, the authors consider the RFDILs of the examined foods in the context of the culinary practices and aesthetics values (those that relate to the culturally held ideas of beauty ascribed to a dish or the processes of its preparation and consumption) of the Indigenous Arctic cuisine in the region of the Bering Strait, and in the broader dynamics of food and culture.